Flucloxacillin, a New Isoxazolyl Penicillin, Compared with Oxacillin, Cloxacillin, and Dicloxacillin - Sutherland, R. (1970)
Flucloxacillin, a new isoxazole penicillin, is active against penicillinase-producing strains of Staphylococcus aureus and is well absorbed in man after oral and intramuscular administration. Compared with isoxazole penicillins in current clinical use—namely, oxacillin, cloxacillin, and dicloxacillin—flucloxacillin has proved as active against Gram-positive cocci, including penicillin-resistant staphylococci. The extent of binding of flucloxacillin to the protein of human serum was similar to that of oxacillin and cloxacillin and less than that of dicloxacillin. In man flucloxacillin given orally produced total and free serum levels higher than those obtained with oxacillin and cloxacillin; total serum levels similar to those of dicloxacillin, and free levels greater than those of dicloxacillin. Similarly, after intramuscular injection the free serum levels of flucloxacillin were higher than those of oxacillin, cloxacillin, and dicloxacillin.